CONTEMPORARY ISLAMIC LEGAL ISSUES IN SOCIOLOGICAL ANTHROPOLOGY STUDIES - Aminuddin, Aminuddin (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
This study aims to examine contemporary Islamic legal issues through sociological and anthropological perspectives, focusing on socio-cultural dynamics that affect the understanding, application, and transformation of Islamic law in modern society. Islamic law, like other legal systems, underwent reform as part of its adaptation to the development of society. The reform of Islamic law is also influenced by contemporary issues, such as: technology, the development of knowledge, and the development of international law. In general, reform in Islamic law refers to two major methods, namely intra-doctrinal reform and extra-doctrinal reform. The research method used is normative juridical, while the primary data comes from a literature study of related legal materials. The results of the study show several Contemporary Issues of Socio-Anthropological Islamic Law, including women's iddah in the modern era, the fate of children born out of marriage, interfaith marriages and women as leaders. This research contributes to a broader understanding of the relationship between Islamic law, social structure, and culture, and offers a theoretical framework for the development of Islamic law in a contemporary context..